Application of meso- and fracture mechanics to material affected by a network of thermal fatigue cracks; International Journal of Fatigue; Vol. 76 : Fatigue Mechanism and Structural Integrity: Advances and Applications - Panin S. V. Sergey Viktorovich; Marushchak P. O. Pavel Orestovich; Lyubutin P. S. Pavel Stepanovich; Konovalenko I. V. Igor Vladimirovich; Ovechkin B. B. Boris Borisovich (2015, 2015)
Title screen